Once the American dream : inner-ring suburbs of the metropolitan United States - Hanlon, Bernadette, 1969- (Book collections on Project MUSE., 2010)
At one time, a move to the suburbs was the American Dream for many families. However, despite the success of Levittown, NY, impoverished "inner-ring" suburbs-those closest to the urban core of metropolitan cities-like Lansdowne, MD, are in decline. As aging housing stock, foreclosures, severe fiscal problems, slow population growth, increasing poverty, and struggling local economies affect inner-ring suburbs, what can be done to save them?Once the American Dream analyzes this downward trend, examining 5,000 suburbs across 100 different metropolitan areas and census regions in 1980.